(untitled) (Comprehensive Journal of Science, 2026)
This study aims to analyze the impact of artificial intelligence on the transformation of operational performance in seaports.amid the growing challenges of global trade and supply chain complexity The study adopts a descriptive -analytical theoretical approach through reviewing the literature and analyzing the relationship between Al applications and the dimensions operational performance with a focus on operational efficiency and operational sustainability.The study concludes that Al applications,such as predictive analytics, intelligent scheduling, and decision support systems contribute to reducing waiting time Improving resource utilization,and lowering costs and emissions thereby supporting the transition toward a data - driven operational model. lt further finds that the effectiveness of this transformation is linked to digital infrastructure integration and the availability of qualified human resources. The study recommends adopting comprehensive digital transformation strategies to enhance competitiveness and sustainability in seaports.